2011
DOI: 10.4315/0362-028x.jfp-10-463
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of ε-Polylysine, Lauric Arginate, or Acidic Calcium Sulfate Applied Sequentially for Salmonella Reduction on Membrane Filters and Chicken Carcasses

Abstract: Salmonella contamination continues to be one of the major concerns for the microbiological safety of raw poultry products. Application of more than one decontamination agent as a multihurdle intervention to carcasses in a processing line might produce greater reductions than one treatment alone due to different modes of action of individual antimicrobials. In this study, all possible two-way combinations and individual applications of ε-polylysine (EPL), lauric arginate (LAE), and acidic calcium sulfate (ACS) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
22
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 27 publications
1
22
0
Order By: Relevance
“…on chicken breast fillets up to 1 log CFU/g during refrigerated storage up to 7 days (Sharma et al, 2013a). Benli et al (2011) reported that sequential spray application of 200 ppm of LAE followed by 30% acidic calcium sulfate reduced Salmonella on chicken carcasses by 2.2 log CFU/ml.…”
Section: Introductionmentioning
confidence: 99%
“…on chicken breast fillets up to 1 log CFU/g during refrigerated storage up to 7 days (Sharma et al, 2013a). Benli et al (2011) reported that sequential spray application of 200 ppm of LAE followed by 30% acidic calcium sulfate reduced Salmonella on chicken carcasses by 2.2 log CFU/ml.…”
Section: Introductionmentioning
confidence: 99%
“…Typical control strategies for Salmonella in raw chicken products involve chemical antimicrobial interventions applied as rinses, primarily at the slaughter facility (1,16). However, this process does not eliminate Salmonella because raw chicken meat can become crosscontaminated or recontaminated during further processing steps (3).…”
mentioning
confidence: 99%
“…It has been reported that lauric arginate (LAE) was effective at reducing Gram negative and Gram positive pathogens, such as Salmonella and Listeria monocytogenes , in different food products (Martin et al ., ; Stopforth et al ., ; Soni et al ., ; Theinsathid et al ., ). The combined spray applications of LAE along with other antimicrobials, such as polylysine and acidic calcium sulphate resulted in significant reduction in Salmonella on chicken carcasses (Benli et al ., ). However, information on the effectiveness of LAE against Salmonella in ground chicken is lacking.…”
Section: Introductionmentioning
confidence: 97%